Characterization of a Novel Thermostable Nuclease Homolog (Nuc(M)) in a Highly Divergent Staphylococcus aureus Clade - Schaumburg, Frieder; Pauly, Maude; Schubert, Grit; Shittu, Adebayo (Journal of Clinical Microbiology, 2020)
Vol, 52. Number 1, p. 4036 – 4038